Anatomies of the Gospels and beyond : essays in honor of R. Alan Culpepper - Culpepper, R. Alan.; Parsons, Mikeal C. 1957- (Biblical Interpretation Series, 2018)
Anatomies of the Gospels and Beyond is an edited volume structured around essays that focus on one of the four canonical Gospels (and Acts) and/or theoretical issues involved in literary readings of New Testament narrative. The volume is intended to honor the legacy of R. Alan Culpepper, Emeritus Professor and Former Dean at Mercer University's McAfee School of Theology. The title of the volume (which alludes to the title of Culpepper's ground-breaking monograph, Anatomy of the Fourth Gospel ) and the breadth of the essays are apt reflections of his research interests over his academic career of over forty years. The twenty-five contributors are internationally recognized experts in New Testament studies; thus, the essays represent a snapshot of current research.